A revisão do regime jurídico da capacidade civil da pessoa natural e a valorização da autonomia existencial da pessoa com deficiência: a efetividade do artigo 85 da Lei Brasileira de Inclusão - Sousa, Felipe Soares de (2019)
The law Nº. 13,146/2015, which establishes the Brazilian Law on the Inclusion of Persons with Disabilities, has become part of the legal system in order to adapt the national legislation to the international parameters incorporated by the Brazilian State, requiring respect for the dignity of persons with disabilities in the various areas of private life and social relations. Article 85 of the referred law, which, in an innovative and central point to this research, restricts the effects of curatorship to acts related only to patrimonial rights, making it impossible for the legal representative of the person with disabilities to intervene in order to exercise existential acts, such as those related to the rights to own body, sexuality, marriage, privacy, education, health, work and voting. Considering the large number of people who will be directly affected by the normative changes in the protection system of persons with disabilities and the various controversies that have arisen in the legal community regarding the effectiveness of the norms that promote true revision of the legal regime of the civil capacity of the natural person, this research is based on the need to seek the interpretation and application of the private law in harmony with the current constitutional order